IGFBP-5 regulates muscle cell differentiation by binding to IGF-II and switching on the IGF-II auto-regulation loop - Ren, Hongxia (The Rockefeller University Press, 2008)
IGF-II stimulates both mitogenesis and myogenesis through its binding and activation of the IGF-I receptor (IGF-IR). How this growth factor pathway promotes these two opposite cellular responses is not well understood. We investigate whether local IGF binding protein-5 (IGFBP-5) promotes the myogenic action of IGF-II. IGFBP-5 is induced before the elevation of IGF-II expression during myogenesis. Knockdown of IGFBP-5 impairs myogenesis and suppresses IGF-II gene expression. IGF-II up-regulates its own gene expression via the PI3K-Akt signaling pathway. Adding IGF-II or constitutively activating Akt rescues the IGFBP-5 knockdown-caused defects. However, an IGF analogue that binds to the IGF-IR but not IGFBP has only a limited effect. When added with low concentrations of IGF-II, IGFBP-5 restores IGF-II expression and myogenic differentiation, whereas an IGF binding–deficient IGFBP-5 mutant has no effect. These findings suggest that IGFBP-5 promotes muscle cell differentiation by binding to and switching on the IGF-II auto-regulation loop.